Density and partial molar volume of Sodium Dodecyl Sulfate in presence and absence of Sodium Sulfate and Zinc Sulfate in distilled water - Limbu, Kuber; Shah, Sujit Kumar; Bhattarai, Ajaya (BIBECHANA, 2018)
The precise measurements of density of sodium dodecyl sulfate (SDS) in distilled water and in presence of 0.01M Na2SO4 and 0.01M ZnSO4 atroom temperature were measured by Ostwald-Sprengel type pycnometer. The density of SDS in distilled water was found lower than the density of SDS in Na2SO4 and ZnSO4 solutions whereas the density of SDS in the presence of ZnSO4 is higher than the density of SDS in the presence of Na2SO4. The partial molar volume of SDS in distilled water was obtained higher than in presence of Na2SO4 and ZnSO4 solutions. BIBECHANA 16 (2019) 131-136